INFLUENCE OF FOOD ADDITIVES COMPLEX ON THE MORPHOLOGY OF VILLI OF THE RATS’ DUODENUM MUCOSA - Yeroshenko, G.A.; Grygorenko, A.S.; Shevchenko, K.V.; Lysachenko, O.D.; Riabushko, O.B.; Pyvovar, N.M.; Klepets, O.V. (World of Medicine and Biology, 2022)
The study presents the findings of the study of the effect of food additives, namely, monosodium glutamate, sodium nitrite and Ponceau-4R on the morphological state of the components of the villi of the rats’ duodenal mucosa. The study was aimed at establishing the dynamics of changes in the metric parameters of the components of the villi of rats’ duodenal mucosa in normal conditions and under the action of the complex of food additives. It has been found that consumption of the complex of food additives leads to changes in the metric values of the height and width of the villi, which at the early stages of the experiment leads to a decrease in their mean values due to the immediate direct action on the mucous membrane with subsequent development of inflammatory reaction and edema, which will lead to an increase in metric values and a decrease in the number of epithelial cells of the villus. Adaptive mechanisms do not fully restore the values of the morphometric study, which is manifested by a decrease in the height of the villi by 20.25 % compared with the control group with an increase in the number of enterocytes with brush border and a decrease in the number of goblet cells by 44.41 %.
Keywords: food additives; duodenum; villus; mucous membrane; rats